Continuous Adaptive Evolution of a Fast-Growing Corynebacterium glutamicum Strain Independent of Protocatechuate - Graf, Michaela; Haas, Thorsten; Müller, Felix; Buchmann, Anina; Harm-Bekbenbetova, Julia; Freund, Andreas; Nieß, Alexander; Persicke, Marcus; Kalinowski, Jörn; Blombach, Bastian; Takors, Ralf (Frontiers in Microbiology, 2019)
Corynebacterium glutamicum is a commonly applied host for the industrial production of amino acids. While valued for its robustness, it is somewhat inferior to competing strains such as Escherichia coli because of the relatively low growth rate of 0.40 h-1 in synthetic, industrial media. Accordingly, adaptive laboratory evolution (ALE) experiments were performed in continuous cultivation mode to select for a growth-improved host. To ensure industrial attractiveness, this ALE study aimed at a reduction of dependency on costly growth-boosting additives such as protocatechuateic acid or complex media supplements. Consequently, double selection pressures were installed consisting of a steady increase in growth rate demands and a parallel reduction of complex medium fractions. Selection yielded C. glutamicum EVO5 achieving 0.54 h-1 and 1.03 gGlc gCDW-1 h-1 in minimal medium without above mentioned supplements. Sequencing revealed ten prominent mutations, three of them in key regulator genes.